Monitoring the progression of the in vitro selection of nucleic acid aptamers by denaturing high-performance liquid chromatography - El Maarri, Osman (2008)
Monitoring of in-vitro selection experiments is crucial in evaluation of the success and outcome of such approaches. Furthermore, monitoring running in parallel with the selection procedure enables early intervention and adjustment of stringency to achieve the desired activities of the selected nucleic acid species. Here we describe the use of a non-radioactive method that enables monitoring of a SELEX procedure on the basis of sequence diversity. We employ denaturing HPLC and describe for the first time an experimental set-up that is useful both for analysis of the progression of in-vitro selection experiments and for separation of distinct aptamer sequences.